Effect of abiotic factors on sulfidogenic activity of bacteria Desulfuromonas sp. - O. M. Сhaіka; T. B. Peretyatko (Regulatory Mechanisms in Biosystems, 2020)
Sulfur-reducing bacteria are promising agents for the development of new methods of wastewater treatment with the removal of ions of heavy metals and organic compounds. Study of the effect of various environmental factors on the growth and sulfidogenic activity of sulfur-reducing bacteria allows one to investigate the adaptability of these microorganisms to stress factors. The paper deals with the effect of рН, different concentrations of elemental sulfur, hydrogen sulfide and presence of various electron acceptors on the growth and sulfidogenic activity of bacteria Desulfuromonas sp. YSDS-3. The calculation of C/S ratio for sulfur-reducing bacteria Desulfuromonas sp. YSDS-3 was made, with the comparison with similar parameters of sulfate-reducing bacteria. In the medium with elemental sulfur, concentration of hydrogen sulfide increased with the concentration of elemental sulfur. Bacteria Desulfuromonas sp. YSDS-3 accumulated their biomass in the most effective way at the concentration of elemental sulfur of 10–100 mM. In the medium with polysulfide form of sulfur at the neutral pH, bacteria produced hydrogen sulfide and accumulated biomass the best. Hydrogen sulfide at the concentration of 3 mM did not inhibit the bacterial growth, but further increase in the hydrogen sulfide concentration inhibited the growth of bacteria. The bacteria did not grow at the hydrogen sulfide concentration of 25 mM and above. As the concentration of elemental sulfur and cell density increases, sulfidogenic activity of the bacteria grows. Presence of two electron acceptors (S and K2Cr2O7, S and MnO2, S and Fe (III)) did not affect the accumulation of biomass of the bacteria Desulfuromonas sp. YSDS-3. However, under such conditions the bacteria accumulated 1.5–2.5 times less hydrogen sulfide than in the test medium. After 12–24 h of cultivation, different concentrations of elemental sulfur had a significant effect on the sulfidogenic activity. However, during 3–16 days of cultivation, the percentage of effect of elemental sulfur concentration decreased to 31%, while the percentage of effect of cell density increased threefold. Presence in the medium of the electron acceptors (Cr (VI), MnO2, Fe (III)) alternative to elemental sulfur led to a significant decrease in the content of hydrogen sulfide produced by sulfur-reducing bacteria.